What is the impact of previous cholelithiasis on sialolithiasis: A systematic review and meta-analysis - Hamed Mortazavi; Ashkan Tizno; Ali Azadi; Rojin Samani; Negin Firoozi; Parham Hazrati (Elsevier, 2024)
Introduction: A sialolith is a salivary stone usually presenting with swelling and pain in the affected salivary gland, most commonly the submandibular gland. There have been speculations about the association between this condition and other systemic diseases, especially those forming stones, such as nephrolithiasis and cholelithiasis. This systematic review and meta-analysis aimed to summarize the studies assessing the relationship between cholelithiasis and sialolithiasis. Methods: PubMed/MEDLINE, Scopus, Web of Science, and Embase electronic databases were searched according to the keywords related to both disorders without any publication date or language restriction. Case-control and cohort studies evaluating the relationship between salivary and biliary stones were considered eligible. Quality assessment was performed following Newcastle-Ottawa Scale (NOS) for quality assessment of case-control studies. All meta and statistical analyses were performed with Comprehensive Meta-Analysis software. Results: Two studies fully complied with the defined eligibility criteria and were included, both of which were case-control studies using national-scale databases. In both surveys, the prevalence of previous gallstones in patients with sialolithiasis was compared to that of a control group. Though one of the studies found that there is no relationship between sialolithiasis and cholelithiasis, the meta-analysis revealed that previous cholelithiasis is significantly more prevalent among patients with sialolithiasis (P = 0.000), with an odds ratio of 2.04. Conclusion: It seems that cholelithiasis is significantly associated with an increase in salivary stone formation. Therefore, a thorough salivary examination in all patients declaring current or past cholelithiasis is recommended. However, more studies, especially prospective cohorts, are needed to make firmer conclusions.